Good Practices for Construction Regulation and Enforcement Reform : Guidelines for Reformers - International Finance Corporation (World Bank Group, Washington, DC, 2014)
The report's main objective is to provide policy makers, regulators, and the private sector, primarily in emerging economies and developing countries, with a tool for enforcing international best practice and for developing strategies for successful reforms in the area of construction regulation. This paper is divided into the following eight chapters: 1) the importance of construction regulation reform. The first chapter defines three overarching goals of construction-regulation reform and addresses why and how these efforts can pay off; 2) reforms as good regulation not deregulation. This chapter points out that deregulating is not the answer; 3) the distribution and focus of construction regulation reform. Leveraging eight years of data from the doing business reports, this chapter provides an overview of reforms initiated within the doing business scenario and the key regional trends; 4) eight key policies affecting process efficiency, transparency, regulatory outcomes, and costs. This chapter provides a concise description of eight priority policy areas; 5) initiating reform and addressing typical challenges. Based on international experience, this chapter focuses on how to start reforms and covers issues including who should be involved in construction-regulation reform and how reform should be sequenced; 6) an overview of best practices. This chapter summarizes the best practices around four major issues, namely, building codes, procedures and transparency, payment of fees, and measures concerning stakeholder liability and accountability; 7) performance measures and evaluation of building regulatory systems. This chapter defines guiding principles for leading the reform effort and includes a meaningful set of indicators and a framework for monitoring outcomes; and 8) ten case studies. This chapters 10 in-depth case studies round out the discussion.